Understanding Loneliness and Social Exclusion in Residential Centers for Social Inclusion. (5th July 2022) - Arnoso Martínez, Ainara; Pizarro Pacheco, Maribel; Arnoso Martínez, Maitane; Asla Alcibar, Nagore; Elgorriaga Astondoa, Edurne
Abstract: Loneliness and social isolation are widely recognized as one of the most important and deep-rooted problems facing society, with special impact on people who are immersed in processes of social exclusion. The study examined the relationship between loneliness and social exclusion in residential centers. It used phenomenological interviews ( N = 11) to explore the subjective experiences of loneliness among people in residential centers for social inclusion to determine the variables associated with their emergence and development, as well as the factors aggravating or alleviating the influence of loneliness on their lives. The results yielded five themes associated with the loneliness of residents, with an interweaving of different axes of exclusion: (1) loneliness and unfulfilled need for meaningful relationships; (2) family losses and conflicts; (3) the experiences of homelessness and residential centers; (4) the economic dependence, contribution, and social inclusion; and (5) the loneliness associated with marginalization and social stigma. Authors present the implications of these findings on social work and some lines of psychosocial intervention.